Perencanaan dan Pengelolaan Alokasi Dana Desa dalam Pemberdayaan Masyarakat di Kampung Skouw Mabo di Kota Jayapura - Medlin Jovancha Lorenza Fouw; James Modouw; Lazarus Ramandei; Deasy Widyastomo; Julian Wairata (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
Improving the quality of life of the community is the goal of Village Fund Allocation (ADD). Improving the quality of life or improving community welfare, especially in villages, requires training and strengthening community capacity. This is the main pillar in planning and managing Village Fund Allocation (ADD) in Skouw Mabo Village. This research was conducted to determine the planning and management of Village Fund Allocation (ADD) in Skouw Mabo Village and what community empowerment activities use Village Fund Allocation (ADD). The method used in this research is a qualitative method with a descriptive approach and using comparative analysis techniques. The results of this research are the planning and management of Village Fund Allocation (ADD) in Skouw Mabo Village in terms of financial administration, the stages have been implemented in accordance with regulations, but in the planning process it is necessary to pay attention and consider priority activities in the village based on local potential so that activities and budget allocation also according to the needs of the activity. Then, in implementing community empowerment activities, the use of funds has been fully realized based on the number of activities and the size of the budget. However, village governments need to pay attention to activities and allocation of financial resources that are more in line with their budgeting priorities, in order to achieve optimal results, namely making the community prosperous and independent.